Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Semiautomatic and Automatic Cooperative Inversion of Seismic and Magnetotelluric Data - Cuong V. A. Le; Brett D. Harris; Andrew M. Pethick; Eric M. Takam Takougang; Brendan Howe (Surveys in Geophysics, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Using SWAT for sub-field identification of phosphorus critical source areas in a saturation excess runoff region - Michael F. Winchell; Solomon Folle; Donald Meals; Julie Moore; Raghavan Srinivasan; Eric A. Howe (Hydrological Sciences Journal, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)